THE EFFECTIVENESS OF ENGLISH LEARNING THROUGH THE SOCIAL NETWORK SITES IN ENHANCING THE STUDENTS’ SPEAKING COMPETENCE (English Education Journal, 2013)
Penelitian ini menguji penggunaan tindak tutur lewat komunikasi komputer,terutama pesan status jejaring sosial Facebook, untuk berkomunikasi baik dalamjumlah besar maupun antar pribadi. Jumlah pesan status ada 352 yang dihasilkanoleh 20 responden yang diambil dalam 3 kali sehari selama kurang lebih 30 hari.Analisa data menunjukan bahwa pesan status yang sering digunakan adalah‘assertives’ (menegaskan) dan diikuti oleh ‘directives’ (menyuruh). Pesan statusyang muncul sebagai tambahan yaitu ‘jokes’ (gurauan) sebesar 3.13%. Uji samplet-tes berpasangan menunjukan adanya perbedaan pencapaian prestasi yangbermakna antara siswa dengan akses internet yang tinggi dan rendah. Sedangkananalisis faktorial varian menunjukan bahwa ada perbedaan kemampuan berbicarayang bermakna antara siswa yang belajar dengan Facebook dengan siswa yangbelajar secara konvensionalThis research examines the use of speech acts in computer-mediated communication, specificallyin the status messages of the social network site Facebook, to communicate in both amass and an interpersonal medium. A total of 352 status messages created by 20 participantswere captured 3 times daily over 30 successive days. Content analysis of these data revealedthat status messages were most frequently constructed with assertives speech acts, followed bydirectives. Additionally, jokes were integrated into almost 3.13% of these status messages. Thepaired sample t-test revealed there was a significant difference in achievement between the highinternet access students and the low internet access ones. While Factorial Analysis of Varianceshowed that there was a significant difference between the students’ speaking competence byusing social network sites and those who are taught by using a conventional approach